Regulatory cooperation and foreign portfolio investment - Lang, Mark; Maffett, Mark; Omartian, James D.; Silvers, Roger (Journal of Financial Economics, 2020)
We investigate the effect of cross-border regulatory cooperation in the enforcement of securities laws on global-mutual-fund portfolio allocations. Our research design exploits a shock to the Securities and Exchange Commission’s oversight of foreign firms cross-listed on a US stock exchange around the signing of the Multilateral Memorandum of Understanding (MMoU), a non-binding, information-sharing arrangement between global securities regulators. In signatory countries, foreign investment in US-cross-listed firms increases by $110 billion relative to non-cross-listed firms. The strongest effects are for investors facing greater information asymmetries, those from countries closely linked to the US, and non-US foreign investors, suggesting significant spillover effects from international regulatory cooperation.